Cold and Hot Syndromes in Traditional Chinese Medicine: Insights from the Perspective of Immunometabolic Homeostasis - Pan Chen; Bo-Yang Wang; Peng Zhang; Shao Li (World Journal of Traditional Chinese Medicine)
The core principle of diagnosis and treatment in traditional Chinese medicine (TCM) is the identification of different syndromes. Cold and hot syndromes are important elements in TCM theory. Identifying the biological basis of cold and hot syndromes in TCM will help elucidate TCM theories scientifically, thus promoting precise treatment in TCM. Although the biological basis of cold/hot syndromes in TCM remains poorly understood, growing evidence suggests that immunometabolic interactions play an important role in balancing cold and hot syndromes. Immunometabolism involves complex interactions between the immune and metabolic systems. Multilevel mechanisms of interaction between the immune and metabolic systems may underlie many inflammatory diseases and offer substantial therapeutic promise. Therefore, dissecting the relationship between immunometabolism and the biological network of cold/hot syndromes has become a priority. This article reviews the progress of cold/hot syndrome research from the perspective of immunometabolic homeostasis, thus further clarifying cold/hot syndromes in TCM.